Scoping Review: Penegakan dan Perlindungan Hukum Tindak Pidana Cyberbullying pada Anak sebagai Pelaku ataupun Korban - Mohammad Daffa Saifullah; Siti Naharotun Nikmah (CV. ULIL ALBAB CORP, 2025)
The criminal act of cyberbullying involving children has become increasingly widespread in recent years, making it necessary to strengthen law enforcement efforts as well as legal protections for children, both as victims and as perpetrators. This article aims to examine the mechanisms of legal enforcement and child protection concerning cases of cyberbullying committed against children and by children within the Indonesian legal system. The article employs a Scoping Review method by analyzing various relevant scholarly works related to the topic. The findings of the review indicate that Indonesian legislation comprehensively regulates criminal acts of cyberbullying involving children, whether they are the victims or the offenders. The applicable legal framework also prioritizes the protection of children’s rights by mandating diversion measures based on a Restorative Justice approach, ensuring that children do not suffer long-term trauma from their involvement in such cases. However, several challenges remain in preventing cyberbullying, particularly due to limited understanding among the public and relevant stakeholders, as well as inadequate facilities and supporting infrastructure to address the issue effectively.